2005
DOI: 10.2466/pms.100.3.707-715
|View full text |Cite
|
Sign up to set email alerts
|

Mood Alterations following an Indoor and Outdoor Exercise Program in Healthy Elderly Women

Abstract: The purpose of this study was to evaluate the effects of a 12-wk. recreational exercise program on mood state of 55 sedentary elderly women, ages 60 to 75 years, as well to examine the minimal amount of weekly exercise needed to produce these changes. The variables comprising mood state were Positive Engagement, Revitalization, Tranquility, and Physical Exhaustion. Subjects were allocated to three exercise groups (n = 15 each) and one control group (n = 10). Exercise was performed for 45 min. three times, twic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 19 publications
0
17
2
7
Order By: Relevance
“…Eleven studies were included in the second group, which examined the effect of strength training on affect [17,18,20,29,49,57,[65][66][67][68]74], and 15 studies on non-specific physical activity or mindful activities such as yoga or Tai Chi were included in the third group [4,7,8,10,15,16,18,30,40,47,41,56,58,75,77]. One study [57] compared aerobic and resistance training to a control group in reducing depression and thus was included in both the first and second group.…”
Section: Review Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies were included in the second group, which examined the effect of strength training on affect [17,18,20,29,49,57,[65][66][67][68]74], and 15 studies on non-specific physical activity or mindful activities such as yoga or Tai Chi were included in the third group [4,7,8,10,15,16,18,30,40,47,41,56,58,75,77]. One study [57] compared aerobic and resistance training to a control group in reducing depression and thus was included in both the first and second group.…”
Section: Review Of the Studiesmentioning
confidence: 99%
“…Five of those six [4,7,15,30,75] reported affective improvements in addition to physiological improvements. However, four of the nine studies which did not assess physical improvement [16,41,47,77] reported affective improvement, and two of the nine [8,40] reported partial improvements.…”
Section: Studies Applying General Non-specific Physical Activitymentioning
confidence: 99%
“…The contribution of leisure activities to promoting health of the elderly is necessary and important [14]. Creative activities and events, in conclusion, not only play an educational role for the elderly, giving them the opportunity to socialize, but also highlight their personality elements and abilities, helping them to develop skills for the adoption of healthy attitudes and behaviors [23].…”
Section: Resultsmentioning
confidence: 99%
“…Visits to local markets, shopping in department stores, volunteer programs, clubbing and, taking part in centers for the open elderly protection, can increase the level of elderly activity and help them sustaining their physical and mental stimulation [14]. A well-designed leisure program for the elderly does not only help them to eliminate the monotony of life, but gives them also the opportunity to live new things and share their thoughts and experiences with peers.…”
Section: Leisure Activity Of the Elderlymentioning
confidence: 99%
See 1 more Smart Citation